Adani Power Limited (B) : renegotiating long-term energy contracts - Pandey, Ajay (London : SAGE Publications Ltd, 2017)
This three-part case series covers a period of over three years during which Adani Power Limited, an independent power producer in India tried to obtain financial relief after having entered into three long-term contracts of 25 years to supply electricity at a fixed price for a total capacity of 3424 MW.
Originally published: Pandey, A. (2014). Adani Power Limited (A): Renegotiating Long-Term Energy Contracts. PSG0114. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Adani Power Limited -- Case studies; Electric power-plants -- India -- Case studies; Energy industries -- India -- Case studies; Energy policy -- India -- Case studies